Studi Literatur: Identifikasi Faktor - Faktor yang Mempengaruhi Perilaku SADARI Sebagai Deteksi Dini Kanker Payudara - Sofia Ananda Mutiara Sari; juwitasari; Tri Lestari Handayani; Ririn Harini (Indonesian Health Science Journal, 2022)
Background: mortality and morbidity rates from breast cancer in 2020 reached 65.5% of the population in Indonesia. Lack of early detection causes delays in treatment which will have an impact on the patient's prognosis getting worse. BSE/ Breast Self-Examination (BSE) is a simple examination or early detection of breast cancer itself. Purpose: This study aims to identify the factors that influence Breast Self-Examination (BSE) behavior and what factors predominate in women performing BSE based on a Literature Study. Method: The design of this research is Literature Study. The sample of this study was 11 journals according to the inclusion criteria and fulfilled the JBI quality assessment of journals. Search data through Pubmed, Biomed Central, EBSCOhost, and ScienceDirect websites. The Boolean Logic used is “Influence OR Impact OR Affect AND Knowledge OR Attitude OR Culture OR Education OR Skills OR Support OR Facilities AND Behavior AND Breast Self-Examination OR Breast Self-Exams AND Breast Cancer” and has been checked using the MesH term. Results: Predisposing factors (Knowledge, Attitude, Cultural Values, Perceptions, Individual Characteristics). Supporting or driving factors (Skills, Resources, Environment), and other factors (Discomfort and Awareness) are factors that influence BSE/Breast Self-Examination behavior in the early detection of Breast Cancer. Conclusion: Literature studies based on journals that have been analyzed are factors that influence BSE behavior in women. The factors that most dominate women performing BSE are predisposing factors which include Knowledge Factors, Attitudes, Cultural Values, Perceptions, and Individual Characteristics, which are known through data analysis using the exposition method.